Mnenje študentov Fakultete za šport o šoli v naravi - Kodrnja, Eva (Šport (Ljubljana), 2018)
The purpose of this study was to examine students' opinion about activities and quality of implementation of different schools in nature they participated during their schooling. The sample included 145 students enrolled in Grade-2 and Grade-3 at Faculty of Sport. Answers were obtained through online survey. At primary school the most common types were swimming and winter school in nature, while at high school the most common type was sports week. The most common reason for non-participation was the lack of financial resources. Students reported that they liked the social connections and the new environment that provide them learning about different parts of Slovenia the most. On the other hand, they didn't like competitions, schedule and food. Females evaluated social component and accommodation statistical higher and the competitions statistical lower than males. Students evaluated organization of different activities very high in primary school and much lower in high school.
Keywords: organizacija; osnovne šole; stroški; šola v naravi; šport; študenti; vsebine; vzgoja in izobraževanje